Identifying Learning Methods of Arabic Reading Skills in Pesantren in Indonesia: Identifikasi Metode Pembelajaran Keterampilan Membaca Bahasa Arab di Pesantren di Indonesia - Abdurrahman; Dhiauddin; Naser Ali Abdulghani (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Arabic, as the language of the Quran and Hadith, plays a central role in gaining a deep understanding of Islamic teachings. In the context of Islamic boarding schools (pesantren), the ability to read Kitab Kuning is a fundamental skill for students. This research aims to identify, compare, and conduct an in-depth analysis of various methods of teaching Kitab Kuning reading that have been implemented in various pesantren. Through a qualitative and bibliometric approach, this study examines seven learning methods most commonly found in the relevant literature. A comparative analysis is conducted to reveal the unique characteristics, advantages, and disadvantages of each method, both those rooted in classical traditions and those adopting modern approaches. The results of this study are expected to make a significant contribution to the development of curricula and the practice of Arabic reading instruction in pesantren. By understanding the strengths and challenges of each method, teachers and pesantren administrators can select and adapt the most suitable methods for the characteristics of students and learning objectives. Furthermore, this research is also expected to serve as a reference for further research in the field of Islamic education, especially related to Arabic language learning. Keywords: Kitab Kuning, Learning Method, Pesantren, Reading Skills.